1997
DOI: 10.1038/eye.1997.125
|View full text |Cite
|
Sign up to set email alerts
|

Nasal administration of retinal antigens maintains immunosuppression of uveoretinitis in cyclosporin-a-treated lewis rats: Future treatment of endogenous posterior uveoretinitis?

Abstract: Methods: Female Lewis rats were immunised with retinal extract (RE) and then treated as follows. Group 1 received no specific therapy and served as control; group 2 were fed CsA from day 7 to day 20 post immunisation; group 3 received inhalational tolerance therapy with RE in addition to CsA; tolerance therapy was continued after day 20 when CsA was stopped.Experiments varying the timing and dosage of both tolerising and immunising antigen were also performed, the details of which are described. Incidence, day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…S-antigen (S-Ag), interphotoreceptor retinoid binding protein (IRBP), or retinal extract (RE; containing a mixture of these and other soluble uveitogenic antigens) induce tolerance to S-Ag, IRBP, or RE induced EAU 59 28 RE was prepared as described9 by hypotonic lysis of freshly dissected bovine retinas in the dark. S-Ag and IRBP were purified from retinal extract under aseptic conditions and filter sterilised as previously described 29.…”
Section: Methodsmentioning
confidence: 99%
“…S-antigen (S-Ag), interphotoreceptor retinoid binding protein (IRBP), or retinal extract (RE; containing a mixture of these and other soluble uveitogenic antigens) induce tolerance to S-Ag, IRBP, or RE induced EAU 59 28 RE was prepared as described9 by hypotonic lysis of freshly dissected bovine retinas in the dark. S-Ag and IRBP were purified from retinal extract under aseptic conditions and filter sterilised as previously described 29.…”
Section: Methodsmentioning
confidence: 99%
“…A later report 14 suggested that peripheral tolerance could still be induced with a nasal tolerant even if cyclosporine was used. However, the nasal administration of antigen could not reliably suppress active disease.…”
Section: Nasal Administration Of Antigenmentioning
confidence: 99%
“…tolerance that involves regulatory cells and is therefore transferable into nontolerant recipients. In adoptive transfer experiments, T cells from donors given autoantigen via mucosal routes are able to suppress the development of autoimmune diseases including diabetes in the nonobese diabetic mouse [17,22±26], experimental autoimmune encephalomyelitis in rats and mice [27±29], collagen-induced arthritis [27] and experimental uveoretinitis [30,31].…”
Section: Mechanisms Of Mucosal Tolerancementioning
confidence: 99%